Approximations between the Policy Cycle Approach, Policy Enactment Theory, and Foucaultian Enunciative Analysis (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2025)
This article aims to present the possibilities for articulating the Policy Cycle Approach and Policy Enactment Theory with Foucaultian Enunciative Analysis in the analytical construction of education policies. The operationalization of Foucaultian concepts such as enunciation and governmentality is presented as a powerful tool for critically analyzing data produced within the contexts of influence, text production, and practice, as well as the contextual dimensions proposed by Policy Enactment Theory. To this end, the article’s writing retraces the theoretical-methodological construction process of a doctoral dissertation in Education that set as its analytical scope the production of the “Schools of the Future” in the Municipal Network of Florianópolis, Santa Catarina, Brazil, and their possible effects on teachers’ work. Through the analysis of official documents and comprehensive interviews with teachers and pedagogical teams from two schools, as well as with two former secretaries of education, it was possible to elaborate the discursive formations that emerge and generate the enunciations of “innovative education” and the “entrepreneurial ethos,” which shape the contexts and dimensions of the Policy Cycle.Keywords: Policy Cycle Approach. Policy Enactment Theory. Governmentality. Enunciative Analysis. Schools of the Future.